MOTILITAS DAN ABNORMALITAS SPERMATOZOA BANGSA PEJANTAN SETELAH PENYIMPANAN - Mohamad Ervandi (Akademika, 2017)
This research aims to study influence of the breed chicken toward motility, abnormality, and durability of live spermatozoa after storage at a temperature 0f 40C. Cement of chicken that using in this research come from 3 chickens male with the different there are chicken laughing , chicken arab , and chicken burma. The design of this research is laboratories experimentaly by using random design complete steel and torrie ( 1991 ) , consisting of 3 treatment and 6 remedial ( the number of cement). The kinds of male chicken that used : P1 = male of chicken laughing, P2 = male of chicken arab, P3 = male chicken burma. The results of the diversity analysis showed that the chicken laughing and chicken arab have an influence significantly (P